Lebenslanges lernen als folge sozio‐ökonomischer trends - Klotz, Michael (Journal of Business Economics and Management, 2003)
Modern societies are faced with lifelong learning as an important challenge. Lifelong learning must be structured and its content must be defined. In order to do this the factors, which influence the need for lifelong learning must be known. These factors ‐ examples are globalization, new markets, new competition, the information society, and knowledge management ‐ will be presented in this article. Article in German. First Published Online: 14 Oct 2010